Australian university students' attitudes towards the use of prescription stimulants as cognitive enhancers: Perceived patterns of use, efficacy and safety. (1st November 2012) - Partridge, Brad; Bell, Stephanie; Lucke, Jayne; Hall, Wayne
Abstract Introduction and Aims Recent, high profile articles in leading science journals have claimed that the enhancement use of prescription stimulants is a common practice among students worldwide. This study provides empirical data on Australian university students' perceptions of: (i) the prevalence of prescription stimulant use by their peers for cognitive enhancement; (ii) motivations for such use; (iii) efficacy; and (iv) its safety. Design and Methods Participants were 19 Australian university students with an average age of 24 who were recruited through emails lists, notice board posters and snowball sampling. Semi‐structured interviews were conducted during 2010 and 2011, recordings transcribed and responses coded using thematic analysis. Results Participants typically did not believe the use of stimulants for cognitive enhancement was common in Australia. Perceived motivations for use included: (i) 'getting ahead' to perform at high levels; (ii) 'keeping up' as a method of coping; and (iii) 'going out' so that an active social life could be maintained in the face of study demands. Australian students were generally sceptical about the potential benefits of stimulants for cognitive enhancement and they identified psychological dependence as a potential negative consequence. Discussion and Conclusions This study is an important first step in understanding the use of stimulants for cognitive enhancement in Australia, amid calls for more widespread use of cognitive enhancing drugs. It is important to conduct further studies of the extent of cognitive enhancement in Australia if we are to develop appropriate policy responses.